Personalised eLearning development environments - Dagger, Declan (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2006)
Personalised eLearning is seen as a key element for next generation educational programmes [DFES, 2005]. The goal of personalised eLearning is to support eLearning content, activities and collaboration, adapted to the specific needs and influenced by specific preferences of the learner and built on sound pedagogic strategies. It seeks to maximise the potential of each learner by providing individually personalised learning experiences. More specifically, it offers the vision of dynamically composed courses which are tailored to an individual’s specific needs, experience, prior knowledge, computing environment, connectivity and communication preferences.
Keywords: Computer Science, Ph.D.; Ph.D. Trinity College Dublin